Nanogap Dielectric Biosensor for label free DNA Hybridization detection - Uda, Hashim; Muhamad Emi Azri, Shohini; Harbant, Singh (Universiti Malaysia Perlis, 2010)
Link to publisher's homepage at http://jere.unimap.edu.my